A Study on the Prevalence and Source of Staphylococci and Methicillin-resistant Staphylococcus aureus Causing Superficial Incisional Surgical Site Infection - Ali, Kameran M.; Al-Jaff, Bahrouz M. A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Staphylococcus aureus and coagulase-negative staphylococci (CoNS) are common causatives of superficial incisional surgical site infection (SSI). The source of the pathogens is still not fully diagnosed whether it is endogenous or exogenous particularly with regard to the extent of its resistance to antibiotics. Therefore, this study is designed to determine the rate of infection, the source of pathogens, and the extent of their resistance to antibiotics. For this purpose, pre-, intra- and post-operative swabs from the nasal and skin of patients undergoing surgeries and samples from the hospital environment have been collected and processed for isolation and identification of staphylococci. Bacterial analysis and antibiotic susceptibility profiles of the isolates are assessed by unweighted pair group method with arithmetic mean (UPGMA) analysis based on random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) and disc diffusion test for antibiotics susceptibility profile. The microbiological and PCR results indicate that SSIs are found in 113/512 (22.07%), Staphylococcus spp. rated 67/512 (13.09%) of infections. Further analysis indicates that S. aureus, CoNS, and both of them were causes SSI with different rates 41/67 (61.2%), 23/67 (34.3%), and 3/67 (4.5%), respectively. Results of RAPD-PCR for 70 isolates reveal that 52/70 (74.28%) of SSIs are from endogenous source, followed by 10/70 (14.29%) and 8/70 (11.43%) from hospitals acquired and undetermined sources, respectively. Moreover, results of antibiotic susceptibility test reveal that 24/44 (54.5%) of isolates belong to methicillin-resistant Staphylococcus aureus; from both endogenous and exogenous sources with 13/24 (54.17%) and 11/24 (45.83%), respectively.